Detachment of the Amplatzer Device after Interventional Closure of a Mitral Prosthesis Paravalvular Leak - Alexandra Pavel (University Library System, University of Pittsburgh, 2018)
Background: Paraprosthetic leak is a complication of mitral and aortic valve implantation interventions, that can be treated either through a surgical procedure (repair or replacement of the prosthesis) or by means of a less-invasive percutaneous transcatheter approach. Nevertheless, this percutaneous intervention carries complications on its own, one of them being displacement of the occluder device. Results: This is the case of a 66-year-old patient, with a clinical history of two mitral valve replacement procedures, who presented with dyspnea, fatigue, and peripheral edema. Echocardiographic findings described severe mitral regurgitation due to the presence of a paravalvular leak. Considering the high perioperative mortality, renal and respiratory impairment, and the fact that this reoperation would have been the third cardiac surgery for the patient, percutaneous transcatheter closure of the leak was recommended. Four days after the successful procedure, a checkup echocardiogram revealed the migration of the occluder device to the left atrial cavity. Even though the operative risk was high and the prognosis poor, the only available treatment option was the surgical management that achieved the removal of the device and replacement of the diseased prosthesis. Conclusion: Albeit less invasive, lower risks, and better outcomes, the percutaneous intervention for leak closure has some clinically relevant complications that must be addressed promptly. One of these complications - detachment of the occluder device - even if quite rare, is a significant event that requires immediate surgical or interventional approach. A careful postoperative checkup is therefore essential to detect any complication and to address it directly.